2016
DOI: 10.1074/jbc.m116.721191
|View full text |Cite
|
Sign up to set email alerts
|

Neogenin Facilitates the Induction of Hepcidin Expression by Hemojuvelin in the Liver

Abstract: Hemojuvelin (HJV for humans, and Hjv for mouse), 2 also called repulsive guidance molecule c (RGMc), is a glycosylphosphatidylinositol-linked membrane protein. It belongs to the highly conserved RGM family that also contains RGMa and RGMb. Although RGMa and RGMb are predominantly expressed in the developing and adult central nervous system and are essential for neural development (1), HJV is expressed mainly in the liver, skeletal muscle, and heart and is essential for iron homeostasis (2). Mutations in the HJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 42 publications
1
33
0
1
Order By: Relevance
“…With serum Fe accumulation, TRF saturation increases and TRF dislodges HFE from its overlapping binding sites on TFRC (D’Alessio et al , 2012). HFE then forms an iron-sensing complex with juvenile hemochromatosis type 2 (HFE2), transferrin receptor 2 (TFR2), and bone morphogenetic protein 6 (BMP6), using the cell surface receptor neogenin (NEO1) as a scaffold protein (D’Alessio et al , 2012; Zhao et al , 2016). Complex assembly initiates the canonical BMP signaling pathway, in which SMAD transcription factors induce Hamp transcription.…”
Section: Resultsmentioning
confidence: 99%
“…With serum Fe accumulation, TRF saturation increases and TRF dislodges HFE from its overlapping binding sites on TFRC (D’Alessio et al , 2012). HFE then forms an iron-sensing complex with juvenile hemochromatosis type 2 (HFE2), transferrin receptor 2 (TFR2), and bone morphogenetic protein 6 (BMP6), using the cell surface receptor neogenin (NEO1) as a scaffold protein (D’Alessio et al , 2012; Zhao et al , 2016). Complex assembly initiates the canonical BMP signaling pathway, in which SMAD transcription factors induce Hamp transcription.…”
Section: Resultsmentioning
confidence: 99%
“…HFE further interacts with ALK3 to prevent its ubiquitination and proteasomal degradation, effecting ALK3 stabilization (Wu et al, 2014), which activates BMP/SMAD signaling and hepcidin transcription. Hepcidin induction by the HJV-BMP receptor complex may be facilitated by neogenin that may act as a scaffold by binding to both HJV and ALK3 (Lee et al, 2010; Zhao et al, 2016) and suppressed by SMAD7 (Mleczko-Sanecka et al, 2010) and miR122 (Castoldi et al, 2011). …”
Section: Controlling Supply and Demand: Iron Acquisition For Red Bloomentioning
confidence: 99%
“…Aprotinin is a soluble membrane-impermeable serine protease inhibitor consisting of 58 amino acids. Both inhibit the proteolytic activity of MT2 (47,49,50). We reasoned that if the substrate cleavage is inhibited by both inhibitors, it would indicate that the cleavage takes place after MT2 reaches the plasma membrane.…”
Section: Mechanistic Studies Of Matriptase-2 Activitymentioning
confidence: 99%
“…Eight-week-old MT2 Ϫ/Ϫ mice of both genders were injected intraperitoneally with AAV8-MT2 or AAV8-MT2-⌬Cyto at ϳ8 ϫ 10 11 and ϳ4 ϫ 10 12 genome-particles per mouse, and AAV8-MT2-mask, AAV8-MT2-Ecto, or AAV8-MT2-S/P at ϳ4 ϫ 10 12 genome-particles per mouse, or PBS vehicle as control. Previous studies indicated that expression of either GFP or glutaryl CoA-dehydrogenase, which are unrelated to iron metabolism, by AAV8 vector in mice had no effects on iron homeostasis (47,51). Age-matched WT littermates were included as additional controls.…”
Section: Plasma Membrane Tethering Is Essential For Mt2 Suppression Omentioning
confidence: 99%